1996
DOI: 10.1111/j.1365-2842.1996.tb00902.x
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of canine dimorphism in establishing sex identity: comparison of two statistical methods

Abstract: SUMMARY The occurrence of canine tooth dimorphism in Indian subjects has been investigated and the use of two statistical methods of evaluation compared. These were the methods of N.G. Rao and co‐workers published in 1988 and quadratic discriminant analysis for correct classification of sex. Parameters considered were (i) the mesiodistal width of maxillary and mandibular canines, (ii) the maxillary canine arch width (intercanine distance) and (iii) the mandibular canine arch width. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Discriminant analysis utilises co-variance in addition to S.D., allowing more critical investigation of the data. 11 Interestingly, discriminant analysis of MD measurement of canines gave recognisably greater sex classification accuracy (69.1%) than discriminant analysis of the MCI ( Table 3). The figure is comparable to the 74.3% accuracy obtained by Anderson and Thompson, 13 who also supported the use of MD dimension of canines in sex determination.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Discriminant analysis utilises co-variance in addition to S.D., allowing more critical investigation of the data. 11 Interestingly, discriminant analysis of MD measurement of canines gave recognisably greater sex classification accuracy (69.1%) than discriminant analysis of the MCI ( Table 3). The figure is comparable to the 74.3% accuracy obtained by Anderson and Thompson, 13 who also supported the use of MD dimension of canines in sex determination.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with Sherfudhin and colleagues' implicit observation that statistical treatment of canine measurements affects sex identification outcome. 11 These authors attribute the difference to the statistical basis of Rao et al's MCI 9 and multivariate discriminant analysis. According to them, the former method employs two parameters (MD dimension of canine and inter-canine arch width) to develop a quotient, using which sex is identified.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that men had wider and longer maxillary central incisors than did women, 29,32–38 whereas no gender differences were found in other studies 39–41 . In one study, male patients exhibited from 0.5 to 1 mm greater tooth width than female patients.…”
mentioning
confidence: 84%
“…Width‐to‐length ratios of the maxillary central incisors ranging from 72% to 124% have been recorded in the dental literature 1,29,30,37,46 . It has been suggested that the width‐to‐length ratios of the maxillary anterior teeth were not affected by gender; 37 however, significant gender differences in width‐to‐length proportions were recorded in previous studies 29,41,47 …”
mentioning
confidence: 99%